Arquitectura hospitalaria, propuesta tipológica del nuevo hospital pediátrico de la ciudad de Riobamba – Ecuador 2024 - Orozco Villarroel, Edgar Paul (2024)
This research project introduces a design approach to hospital architecture, considering its historical evolution from ancient Egypt to Christianity. We consider how the concept of hospital has changed and how these infrastructures have solved social and health problems over time, giving rise to various hospital typologies. The analysis of historical references is fundamental to establish criteria and strategies in the design, complying with current regulations. The proposed project seeks to be an architectural icon that integrates harmoniously with its surroundings, prioritizing nature as a central element to improve the users' experience and enhance the quality of life in the area. In short, this proposal aims to create a functional and healing space that contributes to the well-being of the community.